The Influence of Service Quality and Trust on Customer Loyalty with Customer Satisfaction as an Intervening Variable (The Case Of Alodokter Health Services Application) - Gabriel, Vincent; Ellitan, Lena (Program MM Universitas Surabaya, 2025)
Purpose:This study aims to analyze the effect of Service Quality and Trust on Customer Loyalty with Customer Satisfaction as an intervening in the Alodokter Health Service Application in Surabaya. The object of this study is individuals who have and have used the Alodokter Health Service Application, especially those in the city of Surabaya. Method: This research is a causal research using non-probability sampling techniques with purposive sampling. Respondents in this study are respondents who are at least 17 years old, domiciled in the city of Surabaya, who own and have used the Alodokter Health Service Application more than once in the last six months to one year. The data analysis tool used in this study is Partial Least Square with the SmartPLS 3.0 program application. Result: The results of this study show that Service Quality has a positive and significant effect on Customer Satisfaction. Trust has a positive and significant effect on Customer Satisfaction. Customer Satisfaction has a positive and significant effect on Customer Loyalty. Service Quality has a positive and significant effect on Customer Loyalty. Trust has a positive and significant effect on Customer Loyalty. Service Quality has a positive and significant effect on Customer Loyalty mediated by Customer Satisfaction. Trust has a positive and significant effect on Customer Loyalty mediated by Customer Satisfaction.